Artificial Intelligence and Money Laundering in The Application of International Criminal Law - Miguel Abel (Journal of Business Crime, 2026)
Objective: This study examines the legal and theoretical issues related to using Artificial Intelligence (AI) for preventing and enforcing money laundering under international and European law. It highlights the conflict between technological advancements and the safeguarding of fundamental rights, especially regarding the EU's 2024 anti-money laundering regulatory package and the AI Act. This work was financially supported by the PID2024-160160OB-I00 project of the Spanish State Research Agency (Ministry of Science, Innovation and Universities), Operational Program FEDER "A way of making Europe"Research Design & Methods: This research examines how different EU regulations and directives on Artificial Intelligence align with each other. It analyzes key concepts such as the Europeanization of criminal law, the principles of legality and proportionality, and the balance between security and liberty. The study uses secondary data from EU legal documents and academic literature.Findings: This research shows that AI can help detect and combat money laundering, but it also poses risks such as opaque algorithms, bias, and privacy violations. The EU 2024 regulatory framework seeks to make the use of AI more humane and trustworthy, but differences in criminal law across countries and the lack of a unified European Criminal Code make enforcement difficult. Concerns remain about the proportionality and legality of sanctions among Member States.Implications: The study highlights the need for continuous legal changes, close human supervision, and a distinct separation of administrative and criminal law for using AI in anti-money laundering systems. It also emphasizes strengthening the alignment of criminal law across Europe for better legal clarity and fairness.Contribution & Value Added: This paper looks at how international and European criminal law is developing in the digital world. It links AI governance with anti-money laundering policies. The paper critically assesses the EU 2024 regulatory framework and offers suggestions for balancing technological innovation with the protection of fundamental rights in the criminal legal system.